2002
DOI: 10.2223/jped.815
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic heart disease: prevention should begin in childhood

Abstract: Introduction: ischemic heart disease has gained importance in developing countries. Although clinical symptoms of the disease just appear during adulthood, prevention should begin in childhood, before the establishment of risk factors. Objective: to review the main risk factors for ischemic heart disease and preventive strategies during childhood. Methods: Medline review between 1985 and 2001, and key references from the studies evaluated. Results: preventive interventions that may start in childhood are descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
0
1
0
11
Order By: Relevance
“…Aumentos de 10-20% nas taxas de obesidade infantojuvenil foram registrados na última década, o que representa ônus significativo para o sistema de saúde pública (3)(4)(5)(6) . Cerca de 50% dos adultos dos Estados Unidos, do Canadá e de alguns países da Europa Ocidental têm perfil de sobrepeso ou obesidade, e em alguns subgrupos populacionais chega a ser superior a 70% (4) .…”
Section: O Problema Da Obesidade Infantojuvenilunclassified
See 2 more Smart Citations
“…Aumentos de 10-20% nas taxas de obesidade infantojuvenil foram registrados na última década, o que representa ônus significativo para o sistema de saúde pública (3)(4)(5)(6) . Cerca de 50% dos adultos dos Estados Unidos, do Canadá e de alguns países da Europa Ocidental têm perfil de sobrepeso ou obesidade, e em alguns subgrupos populacionais chega a ser superior a 70% (4) .…”
Section: O Problema Da Obesidade Infantojuvenilunclassified
“…No Brasil a situação não é diferente. Estudos epidemiológicos bem delineados, realizados em diferentes cidades brasileiras, demonstraram que a obesidade infantil é também uma grande preocupação em nosso país (3,(6)(7)(8) .…”
Section: O Problema Da Obesidade Infantojuvenilunclassified
See 1 more Smart Citation
“…shown that hemodynamic changes are observed in these individuals as early as in the second decade of life, or even earlier, 6,7 hence the importance of routine evaluation of BP in childhood, 8 according to the recommended protocol. 9 There is evidence that protocols are implemented in the pediatric care routines, but there is a discrepancy between the used protocols and the prevalence of hypertension or elevated BP found in the population studies.…”
Section: Introductionmentioning
confidence: 99%
“…Os distúrbios nutricionais na infância estão relacionados com o desenvolvimento de doenças crônicas não-transmissíveis na vida adulta, sendo, portanto, a infância fase de extrema importância para ações de promoção da saúde (6,7) . O cenário detectado no Brasil pode ser consequência de modificações no padrão alimentar da população.…”
Section: Introductionunclassified